Answer:
(2a - 5) • (3a - 2)
step by step explanation:
Step-1 : Multiply the coefficient of the first term by the constant 6 • 10 = 60
Step-2 : Find two factors of 60 whose sum equals the coefficient of the middle term, which is -19 .
-60 + -1 = -61
-30 + -2 = -32
-20 + -3 = -23
-15 + -4 = -19 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -15 and -4
6a2 - 15a - 4a - 10
Step-4 : Add up the first 2 terms, pulling out like factors :
3a • (2a-5)
Add up the last 2 terms, pulling out common factors :
2 • (2a-5)
Step-5 : Add up the four terms of step 4 :
(3a-2) • (2a-5)
Which is the desired factorization
Final result :
(2a - 5) • (3a - 2)